Self-reported food safety behaviors in independent ethnic restaurants: an application of the Social Cognitive Theory - Boutros, Basem (Kansas State University, 2018)
Ethnic foods have gained in popularity and have become mainstream in the diet of most Americans. However, researchers have noted that ethnic food, specifically food served in ethnic restaurants, has been associated with foodborne outbreaks. Little has been done using the Social Cognitive Theory to predict food safety behaviors, especially in independent ethnic restaurants. The purpose of this study was to determine whether self-efficacy, self-regulation, outcome expectations, and environmental determinants are predictive of self-reported food safety behaviors in independent ethnic restaurants. Utilizing a thorough literature review and results of five focus group and group interviews, a questionnaire was developed. The questionnaire was translated to Chinese and Spanish and back-translated to English to ensure consistency. After pilot-testing, a multistage random sampling technique was utilized to collect data, targeting a total of 150 food handlers from independent Mexican and Chinese restaurants. A total of 204 food handlers responded, but due to incomplete data or responses from non-food handlers, 201 responses were usable for a response rate of 80.4%. A multiple regression analysis investigated the prediction of food safety behavioral intentions based on the respondents’ self-efficacy, self-regulation, outcome expectations, and environmental determinants and found the model was significant (F = 75.246, p = 0.002). The significant independent variables in the model were self-regulation (β = 0.467, p = 0.001), environmental determinants (β = 0.181, p = 0.011), and outcome expectations (β = 0.152, p = 0.018), which explained about 60.6 % of the variance in food safety behavioral intentions. Self-efficacy was not significant (β = 0.078, p = 0.219). A mediation analysis showed that behavioral intentions are a significant mediator of the relationships between self-efficacy and self-reported food safety behaviors (b = 0.24, CI [0.161, 0.336], self-regulation and self-reported food safety behaviors (b = 0.252, CI [0.155, 0.366]), outcome expectations and self-reported food safety behaviors (b = 0.355, CI [0.247, 0.469]), and environmental determinants and self-reported food safety behaviors (b = 0.269, CI [0.172, 0.393]). Implications, limitations, and direction for future research were discussed.
Keywords: Social Cognitive Theory; Independent ethnic restaurants; Self-reported food safety behaviors; Ethnic food; Food handlers